2014
DOI: 10.1007/s10951-014-0382-0
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling parallel batch jobs in grids with evolutionary metaheuristics

Abstract: In this paper we propose an efficient offline job scheduling algorithm working in a grid environment that is based on a relatively new evolutionary metaheuristic called generalized extremal optimization (GEO). We compare our experimental results with those obtained using a very popular evolutionary metaheuristic, the genetic algorithm (GA). The scheduling algorithm implies two-stage scheduling. In the first stage, the algorithm allocates jobs to suitable machines of a grid; GEO/GA is used for this purpose. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Such heuristics produced good results for small problem and system sizes. However, to effectively deal with the NP-hard JSP problem in complex HCS platforms, several meta-heuristic based offline solutions are developed over the years [14][15][16][17] [30]. The major focus of the research was on scheduling independent jobs i.e.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Such heuristics produced good results for small problem and system sizes. However, to effectively deal with the NP-hard JSP problem in complex HCS platforms, several meta-heuristic based offline solutions are developed over the years [14][15][16][17] [30]. The major focus of the research was on scheduling independent jobs i.e.…”
Section: Related Workmentioning
confidence: 99%
“…If a job is non-coallocated one, then PEs from first slowest cluster in the sorted available cluster list will be allocated to the job otherwise PEs across the multiple clusters starting from slowest cluster can be allocated to the job (Line [15][16][17][18][19]. In nutshell, Resource allocation heuristic tends to avoid unnecessary co-allocations to reduce communication slowdown to reduced actual execution time, by allocating single cluster PEs and tries to allocate low computation power resources to jobs to further reduce energy consumption.…”
Section: Solution Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also demonstrated the performance guarantee of any list-scheduling algorithm for the P|size j |C max problem should be no less than 2. Switalski and Seredynski (2015) proposed an evolutionary metaheuristic algorithm called the generalized extremal optimization (GEO) to solve a machine scheduling problem with multi-processor tasks. In their study, each machine is defined to have a batch of processors that can work in parallel, and different machines may have different numbers of processors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, (1) in diagnosable microprocessor systems, a task must be processed by at least two processors at the same time (Krawczyk and Kubale, 1985); (2) in semiconductor circuit design workforce planning, a design project may need a group of people (Chen and Lee, 1999), (3) in the quay crane scheduling problem of container terminals, a ship requires more than one crane to handle (Trkoullar et al, 2014) and (4) in parallel batch jobs scheduling problems of grid computing environments, a computing task may run on several processors that work in parallel (Switalski and Seredynski, 2015). This paper studies a Parallel Machine Scheduling problem which allows tasks to be processed on more than one machine.…”
Section: Introductionmentioning
confidence: 99%